Scientific productivity: An exploratory study of metrics and incentives - Lindner, Mark D.; Torralba, Karina D.; Khan, Nasim A. (PLOS ONE, 2018)
Competitive pressure to maximize the current bibliometric measures of productivity is jeopardizing the integrity of the scientific literature. Efforts are underway to address the ‘reproducibility crisis’ by encouraging the use of more rigorous, confirmatory methods. However, as long as productivity continues to be defined by the number of discoveries scientists publish, the impact factor of the journals they publish in and the number of times their papers are cited, they will be reluctant to accept high quality methods and consistently conduct and publish confirmatory/replication studies. This exploratory study examined a sample of rigorous Phase II-IV clinical trials, including unpublished studies, to determine if more appropriate metrics and incentives can be developed. The results suggest that rigorous procedures will help reduce false positives, but to the extent that higher quality methods are accepted as the standard of practice, the current bibliometric incentives will discourage innovative studies and encourage scientists to shift their research to less informative studies of subjects that are already being more actively investigated. However, the results also suggest that it is possible to develop a more appropriate system of rewards. In contrast to the current bibliometric incentives, evaluations of the quality of the methods and reproducibility of the results, innovation and diversity of thought, and amount of information produced may serve as measures and incentives that maintain the integrity of the scientific literature and maximize scientific progress.